Improving Reading Comprehension Using Snowball Throwing Technique among Students at One of Public Vocational High School in EFL Context - Queena Sehara Jeanery; Asma Alhusna; Rahma Dania (English Education and Applied Linguistics Journal (EEAL Journal), 2025)
This research investigates the effectiveness of the Snowball Throwing Technique (STT) in improving students’ reading comprehension. The objective of this study was to determine whether there is a significant difference in students’ reading comprehension before and after being taught using the STT. A quantitative method with a pre-experimental design was employed, involving one randomly selected class of tenth-grade culinary students at one of public vocational high school in Padang. Data were collected using a pre-test and post-test. The mean score of students’ reading comprehension in the pre-test was 57.26, while the post-test score increased to 79.5. Based on the results of the paired t-test, the t-value (8.892) was higher than the t-table value (2.045), indicating a statistically significant improvement. These findings confirm that the Snowball Throwing Technique has a positive effect on enhancing students’ reading comprehension skills. This study concludes that STT can be an effective teaching method to improve students’ engagement and understanding in reading activities. This study contributes to educational research by offering empirical evidence that interactive, student-centred strategies like STT can improve reading outcomes, particularly in vocational school contexts. It supports the integration of collaborative techniques into English language teaching practices.